Impact of monitoring and control in the protection of the rights of the users of public service electric power in Colombia (2013)
This essay on the surveillance and control models in the provision of energy services in Colombia is an analysis of the main mechanisms used to achieve efficient delivery of service delivery and thus to ensure the protection of users rights. This analysis arises because according to the evolution and current complexity of public services in our country and considering that its essentiality affects all the inhabitants of the country, necessarily implies that specialize the monitoring and control functions seeking to ensure access quality public services, sustainability, equity and efficiency in order to meet the basic needs that all people without distinction should have and so fulfill the purpose of developing and project in all its dimensions within a society.